KEWENANGAN KOMISI YUDISIAL DALAM MELAKUKAN TUGAS PENGAWASAN TERHADAP KINERJA HAKIM DI LINGKUNGAN PENGADILAN - Rubiyanto Rubiyanto (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2017)
The existence of the Judicial Commission in the state system in Indonesia is very interesting to study more comprehensively. Based on the above background, it can be a problem as follows: How does the authority of the Judicial Commission in the conduct of monitoring the performance of judges in the court? The method used in this research is normative juridical (normative legal research). Specifications of research used is descriptive analytical. Data obtained from field research is the primary data and secondary data was analyzed qualitatively, ie an analysis of the primary legal materials, secondary law and tertiary legal materials. According to the research fund of the discussion can be concluded that the judicial commission in the state system is based on the Constitution of the Republic of Indonesia Year 1945 has a position as a body that is independent authorized to propose the appointment of justices and have other authorities in order to preserve and uphold the honor, dignity, dignity as well as the behavior of judges. The Judicial Commission has the authority to supervise the performance of judges in a transparent and participatory.